Paediatric Post-Traumatic Tenosynovial Chondromatosis of the Foot: A Case Report - Porčić, Šemsudin; Jokić, Andrej; Todorovac Hodžić, Irma (Scripta Medica, 2025)
Tenosynovial chondromatosis (TC) is a rare benign condition characterised by the formation of cartilaginous nodules from tendon sheaths or articular membranes. It primarily affects the hand and wrist structures. The condition predominantly affects individuals in their thirties to fifties. The post-traumatic TC is not reported in a paediatric patient, to the best of our knowledge. The purpose of this case was to describe a five-year-old girl’s case of TC, which had a highly unusual localisation in the foot following a post-traumatic event. In order to handle this challenging lesion, the clinical presentation, imaging modalities, histopathology and surgical treatment is presented. Performing surgery with wide margins is the gold standard.